دراسة سوسيولوجية تحليلية للمنهج في البحث الاجتماعي - ذياب, سليمة; ضيف, الأزهر (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الورقة إلى تقديم رصيد معرفي للطلبة الباحثين، ونبذة وفكرة – وجيزة- عن مختلف الأسس النظرية والمعرفية لمنهج البحث الاجتماعي. وحتى يدرك الباحث أن القراءة في مجال المنهجية العلمية وعلاقتها بمجال التخصص أمر مهم، ففي القراءة أسس الانطلاق المعرفي إلى المقاربة المنهجية. وفي إطار استكشاف قضايا البحوث النوعية والكمية، ومختلف أشكالها، رأينا أن هناك حاجة إلى النظر في مختلف الأسس النظرية والمعرفية التي تستند عليها البحوث الكمية والكيفية وتجادل حولها علماء الاجتماع؛ ولتحقيق ذلك تطرقنا للعناصر التالية: تعريف المنهج العلمي تعريف منهج البحث الاجتماعي، والعوامل التي دعت لوجود منهج، أنواع منهج البحث الاجتماعي، ثم فصلنا في الأصول المعرفية لمنهج البحث الاجتماعي. Abstract: This article aims to provide a cognitive balance to student researchers, an overview and a - brief - idea on the different theoretical and epistemological foundations of the social research approach. And until the researcher realizes that reading in the field of scientific methodology and its relationship with the area of specialization is important, in reading the foundations of cognitive start to the methodological approach. In the context of exploring the challenges of qualitative and quantitative research, and of its different forms, we have seen that it is necessary to consider the different theoretical and epistemological foundations on which quantitative and qualitative research is based, and the social scientists discuss it. For the existence of a curriculum, of types of social research method, we then separated into cognitive origins from the social research approach.
" Étude analytique susiologique de l'approche de la recherche sociale "
مقال
Keywords: البحث الاجتماعي، المنهج العلمي، المنهج الكمي، المنهج الكيفي.; social research, scientific method, quantitative approach, qualitative approach.